CpG location and methylation level are crucial factors for the early detection of oral squamous cell carcinoma in brushing samples using bisulfite sequencing of a 13-gene panel - Luca Morandi; Davide Gissi; Achille Tarsitano; Sofia Asioli; Andrea Gabusi; Claudio Marchetti; Lucio Montebugnoli; Maria Pia Foschini (Clinical Epigenetics, 2017)
Abstract Background Oral squamous cell carcinoma (OSCC) is usually diagnosed at an advanced stage and is commonly preceded by oral premalignant lesions. The mortality rates have remained unchanged (50% within 5 years after diagnosis), and it is related to tobacco smoking and alcohol intake. Novel molecular markers for early diagnosis are urgently needed. The purpose of this study was to evaluate the diagnostic value of methylation level in a set of 18 genes by bisulfite next-generation sequencing. Methods With minimally invasive oral brushing, 28 consecutive OSCC, one squamous cell carcinoma with sarcomatoid features, six high-grade squamous intraepithelial lesions (HGSIL), 30 normal contralateral mucosa from the same patients, and 65 healthy donors were evaluated for DNA methylation analyzing 18 target genes by quantitative bisulfite next-generation sequencing. We further evaluated an independent cohort (validation dataset) made of 20 normal donors, one oral fibroma, 14 oral lichen planus (OLP), three proliferative verrucous leukoplakia (PVL), and two OSCC. Results Comparing OSCC with normal healthy donors and contralateral mucosa in 355 CpGs, we identified the following epigenetically altered genes: ZAP70, ITGA4, KIF1A, PARP15, EPHX3, NTM, LRRTM1, FLI1, MIR193, LINC00599, PAX1, and MIR137HG showing hypermethylation and MIR296, TERT, and GP1BB showing hypomethylation. The behavior of ZAP70, GP1BB, H19, EPHX3, and MIR193 fluctuated among different interrogated CpGs. The gap between normal and OSCC samples remained mostly the same (Kruskal-Wallis P values < 0.05), but the absolute values changed conspicuously. ROC curve analysis identified the most informative CpGs, and we correctly stratified OSCC and HGSIL from normal donors using a multiclass linear discriminant analysis in a 13-gene panel (AUC 0.981). Only the OSCC with sarcomatoid features was negative. Three contralateral mucosa were positive, a sign of a possible field cancerization. Among imprinted genes, only MIR296 showed loss of imprinting. DNMT1, TERC, and H19 together with the global methylation of long interspersed element 1 were unchanged. In the validation dataset, values over the threshold were detected in 2/2 OSCC, in 3/3 PVL, and in 2/14 OLP. Conclusions Our data highlight the importance of CpG location and correct estimation of DNA methylation level for highly accurate early diagnosis of OSCC.